1997
DOI: 10.7326/0003-4819-126-10-199705150-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Direct Relation between Total Cholesterol Levels and Death from Coronary Heart Disease in Older Persons

Abstract: Elevated total cholesterol level is a risk factor for death from coronary heart disease in older adults, and the apparent adverse effects associated with low cholesterol levels are secondary to comorbidity and frailty. This suggests that excluding older persons from cholesterol screening is inappropriate, but interpretation of screening results in older persons requires clinical judgment. Results from controlled clinical trials are needed to clarify this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
107
2
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(118 citation statements)
references
References 0 publications
5
107
2
4
Order By: Relevance
“…high HDL-C, low LDL-C, and low TG levels) being associated with the risk of cognitive decline. Such lipidic pattern is associated with inflammation, poor nutritional status, and frailty (Corti et al, 1997;Hu et al, 2003) and may thus reflect a change in dietary habits accompanying pathology and/or be a marker for early neurodegenerative changes. In our previous study, TG levels were found associated with a decreased risk of…”
Section: Discussionmentioning
confidence: 99%
“…high HDL-C, low LDL-C, and low TG levels) being associated with the risk of cognitive decline. Such lipidic pattern is associated with inflammation, poor nutritional status, and frailty (Corti et al, 1997;Hu et al, 2003) and may thus reflect a change in dietary habits accompanying pathology and/or be a marker for early neurodegenerative changes. In our previous study, TG levels were found associated with a decreased risk of…”
Section: Discussionmentioning
confidence: 99%
“…Whereas low HDL-cholesterol is predictive of cardiovascular disease even among people >70 years old [29,30], observational studies in the elderly have either shown no predictive effect of plasma LDL-cholesterol or a protective effect of higher concentrations [3][4][5][6]. In a large population-based cohort of elderly people in the USA, 20% of whom had diabetes, the protective effect of higher concentrations of total choles- terol disappeared after adjustment for markers of poor health, suggesting confounding effects of comorbidity and frailty [5]. In the Honolulu Heart Program, in which 3,572 Japanese American men were followed-up prospectively for 20 years, significantly decreasing age-adjusted mortality rates were found for the upper vs the lower quartiles of cholesterol concentrations, particularly in men with persistently low cholesterol values in consecutive examinations [3].…”
Section: Discussionmentioning
confidence: 99%
“…This association is weaker in older people, with an apparent paradoxical protective effect of high concentrations of cholesterol in some observational studies [2][3][4][5][6][7]. Measurement of plasma apolipoprotein (Apo) B and ApoA-I improves the prediction of cardiovascular disease, allowing identification of high-risk individuals who are not identified by the standard lipid profile [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Corti et al 14 concluded from the EPESE data that abnormal cholesterol levels are associated with CVD death in the elderly, and that their exclusion from studies that evaluate the relationship between cholesterol and CVD is improper. In "The Northern Manhattan Study" 15 , the authors infer that high HDL-c is associated with a reduced risk of ischemic stroke in the elderly, and they considered HDL-c as an important modifiable RF for stroke.…”
Section: Introductionmentioning
confidence: 99%